PENDATAAN INFRASTRUKTUR JARINGAN JALAN DI DESA ADAT LOKASERANA, DESA SIANGAN - Ni Made Widya Pratiwi; AA Gede Sumanjaya; Made Sani Damayanthi Muliawan (Universitas Warmadewa, 2022)
Lokaserana Traditional Village is one of the traditional villages parts of Siangan Village. Lokaserana Traditional Village is located in Siangan Village, Gianyar District, Gianyar Regency. The traditional chief, I Ketut Putra Yasa, leads the Lokaserana Traditional Village. Lokaserana Traditional Village Community, Most of them work in the tourism sector. However, because of the pandemic, people have turned to become farmers. The Lokaserana Traditional Village is connected to the village temples, and there is a place of worship, which has the potential to be a religious tourism area. Based on the potential of this area, it has not been accompanied by good road network infrastructure arrangements, especially the maximum utilization of the shoulders, the drainage that has not worked optimally, and the road asphalt in poor condition, especially near village boundaries. Based on this problem, the solutions offered by the PKM Team included: socialization of road shoulder arrangement and repair of drains or culverts. The methods used in this PKM were observation and survey data collection.